Information sources and plaque awareness on denture cleaning practices among denture wearers - Adrianto Budiharjo; Olivia Budihargono (Indonesian Journal of Dental Medicine, 2026)
Background: Denture hygiene is essential for preventing denture stomatitis. Denture cleaning practices may be influenced by health information sources and awareness of denture plaque accumulation. Purpose: To examine the plaque awareness and information sources on denture cleaning practices among denture wearers. Methods: A cross-sectional survey was conducted using a structured questionnaire among 58 denture users aged 65 years and older in Surabaya. Participants were removable denture wearers using acrylic dentures, flexible dentures, or metal framework dentures for at least six months. Denture cleaning practices were categorized into three levels: poor (cleaning dentures using water only or without a specific cleaning technique); moderate (cleaning dentures using a toothbrush with or without toothpaste); and good (cleaning dentures using specialized cleaning agents such as denture cleanser or liquid soap combined with mechanical brushing). Data were examined using descriptive statistics, chi-square analysis, and logistic regression, with p-value < 0.05 considered as significant. Results: Most respondents were aware of plaque accumulation (81.0%) and obtained cleaning information from dentists (91.4%). Cleaning practices were moderate (69.0%) and good (20.7%). Plaque awareness was significantly correlated with better cleaning practices (p=0.048). Logistic regression showed that aware respondents were 5.24 times more likely to perform adequate cleaning (95% CI: 1.00–27.35; p=0.049). Information source was not significantly correlated (p>0.05). Conclusion: Plaque awareness is significantly associated with denture cleaning practices among denture wearers. Educational strategies that enhance awareness of plaque-related risks may improve denture hygiene behaviours.